Identification of susceptibility SNPs in CTLA‐4 and PTPN22 for scleritis in Han Chinese. (16th April 2019) - Li, F.; Ma, X.; Du, L.; Shi, L.; Cao, Q.; Li, N.; Pang, T.; Liu, Y.; Kijlstra, A.; Yang, P.
Summary: The aim of this study was to determine the association between 13 single nucleotide polymorphisms (SNPs) in the cytotoxic T lymphocyte‐associated antigen‐4 ( CTLA4 ) and protein tyrosine phosphatase non‐receptor type 22 ( PTPN22 ) genes with scleritis in a Chinese Han population. We recruited 432 scleritis patients and 710 healthy controls. Four tag SNPs of CTLA4 and nine tag SNPs of PTPN22 were selected using Haploview. Genotyping was performed with the Sequenom MassArray® iPLEX GOLD Assay. Genotype and allele frequency differences were analyzed by χ 2 test and Bonferroni correction. Haplotype analysis was performed to further evaluate the association of these two genes with scleritis. In this study, CTLA4 /rs3087243 G allele frequency and GG genotype frequency were significantly increased in scleritis patients compared to healthy controls [corrected P ‐value ( Pc ) = 0·02, odds ratio (OR) = 1·475, 95% confidence interval (CI) = 1·175–1·851; Pc  = 0·04, OR = 1·546, 95% CI = 1·190–2·008, respectively]. None of the tested SNPs in the PTPN22 gene showed an association with scleritis. Haplotype analysis revealed a lower frequency of a CTLA4 TCAA haplotype (order of SNPs: rs733618, rs5742909, rs231775, rs3087243) ( Pc  = 4·26 × 10 –3, OR = 0·618, 95% CI = 0·540–0·858) and a higher frequency of a PTPN22 TTATACGCG haplotype (order of SNPs: rs3789604, rs150426536, rs1746853, rs1217403, rs1217406, rs3789609, rs1217414, rs3789612, rs2488457) ( Pc  = 2·83 × 10 –4, OR = 1·457, 95% CI = 1·210‐1·754) in scleritis patients when compared to healthy controls. In conclusion, our findings indicate that CTLA4 and PTPN22 might confer genetic susceptibility to scleritis in a Chinese Han population. Abstract : The association between 13 single nucleotide polymorphisms (SNPs) in the cytotoxic T lymphocyte‐associated antigen‐4 ( CTLA4 ) and protein tyrosine phosphatase non‐receptor type 22 ( PTPN22 ) genes with scleritis was investigated in a Chinese Han population. The findings revealed the involvement of a CTLA4 /rs3087243 polymorphism as a predisposing risk factor. A four‐SNP haplotype of the CTLA4 gene was possibly a protective genetic marker for scleritis, and a nine‐SNP haplotype of PTPN22 was found to contribute to the risk of scleritis.